(untitled) (Journal of Fatima Jinnah Medical University, 2019)
Cancer registry is a system devised for collection and analysis of data about patients diagnosed to have malignant tumors/cancer. Cancer along with other communicable diseases has been recognized as major health concern. According to World Health Organization (WHO) projection modeling, its incidence is expected to increase by 100% to 180%.1 Cancer registry is classified as hospital registry (deals with patients diagnosed as and treated for cancer, central registry (population based within a certain geographical area) and special purpose registry (about a particular type of cancer). Dr. Earnest Codman attempted cancer registry program in a limited way in United States in 1926. Differences in nomenclature and classification turned out to be major problem in establishing cancer registry program. This problem was overcome by development of standard classification and nomenclature by the combined effort of American society of clinical pathologists and American college of Surgeons.2